Fabrication of Hollow Needle Tips with Nanoholes by Plasma Maskless Processing and Calculation and Detection of Complex Surface Edges - Zuocai Dai; Sha Zhou; Tongguang Yang; Yanpeng Wang (Advances in Materials Science and Engineering)
The plasma maskless processing method combines the advantages of plasma etching and scanning probe processing, such as high etching efficiency, wide range of applicable materials, and high resolution. This method is based on the probe driving and detection of piezoelectric thin films, which enables all probes in the array to be processed completely independently, greatly improving the overall processing efficiency, and can effectively etch specific nano-scale regions of various materials. And it provides an effective solution for efficiently processing small batches of multi-variety micro-nano devices. In this study, a hollow needle tip with nanoholes was fabricated by plasma maskless processing, and use edge computing to calculate the complex surface shape of the needle tip. By establishing a plasma reactor, using the calculation method of the complex surface edge of the needle tip, and testing the stability of the processed nanotip by means of filling air pressure and power excitation in the experiment. The results show that when the breakdown voltage SF6 discharges, with the increase of air pressure, the breakdown voltage of the arrester first decreases and then increases gradually, and it is the smallest at 5 kPa and reaches the optimal 490 V, (PD) m = 0.5 Pa·m. And the Ar reaction ionization potential (15.76 eV) and excitation potential (11.53 eV, 11.72 eV) are lower than the splitting potential (≥16 eV) of SF6. As time goes on, high-energy particles are neutralized with the vessel wall, so the ion concentration is gradually smaller, sparse between 200 and 250, and increases from 100 to 300, which is close to the peak value, according to the gradual increase of the discharge voltage. The data obtained from the experimental test proves the reliability of the nanotips prepared in this study, and the properties remain stable under different breakdown voltages. Therefore, the nanohole hollow tip processed by maskless scanning plasma in this study has reached the standard of process use and has important application significance.